Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3109/13880209.2015.1066398
|View full text |Cite
|
Sign up to set email alerts
|

Crataegus songaricamethanolic extract accelerates enzymatic status in kidney and heart tissue damage in albino rats and itsin vitrocytotoxic activity

Abstract: Crataegus songarica methanol extract has a potential antioxidant effect as it protects the kidney and heart tissue against CCl4-induced toxicity, prevents DNA damage and showed strong anticancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…C. oxyacantha alcoholic extract produced an antiarrhythmic effect that was induced by digoxin in Wistar rats; however, in the clinical use of this extract, the hypotensive effect should be considered (Alp et al, 2015). Another in vivo study reported that administration of methanolic C. songarica extract at the dose of 300 mg/kg body weight to albino rats with CCl 4 -iduced toxicity significantly decreased serum creatinine, urea, and cholesterol, malondialdehyde (MDA) in kidney and heart tissues, along with recovery in antioxidant enzyme levels (Ganie et al, 2016). It was also reported that standardized Crataegus extract prevented DOCA-salt-induced hypertension and alteration of cardiac, vascular and renal structure and function in rats (Schini-Kerth et al, 2015).…”
Section: Venskutonismentioning
confidence: 99%
See 1 more Smart Citation
“…C. oxyacantha alcoholic extract produced an antiarrhythmic effect that was induced by digoxin in Wistar rats; however, in the clinical use of this extract, the hypotensive effect should be considered (Alp et al, 2015). Another in vivo study reported that administration of methanolic C. songarica extract at the dose of 300 mg/kg body weight to albino rats with CCl 4 -iduced toxicity significantly decreased serum creatinine, urea, and cholesterol, malondialdehyde (MDA) in kidney and heart tissues, along with recovery in antioxidant enzyme levels (Ganie et al, 2016). It was also reported that standardized Crataegus extract prevented DOCA-salt-induced hypertension and alteration of cardiac, vascular and renal structure and function in rats (Schini-Kerth et al, 2015).…”
Section: Venskutonismentioning
confidence: 99%
“…Ethanolic extract of C. microphylla flowers and leaf buds demonstrated cytotoxic and antiproliferative activity against HeLa cell (IC 50 = 0.871 mg/mL) and least cytotoxicity on normal human peripheral mononuclear cells (Bura et al, 2016). Methanol, ethanol and ethyl acetate extracts of C. songarica K. Koch exhib-ited potent in vitro anticancer activity on MCF-7, HeLa, HepG2, SF-295, SW480 and IMR-32 cancer cell lines with IC 50 values of 28.57-85.106 μg/mL, while methanol extract demonstrated protective activity for albino rats' kidney and heart tissue against CCl 4induced toxicity in vivo (Ganie et al, 2016). C. monogyna extract at 100-75 μg/mL concentrations exhibited better antiproliferative activity against C6 cell lines than 5-flurouracil drug (5-FU) and cisplatin, and also demonstrated considerable antiproliferative activity against HeLa cells (Yaglioglu et al, 2016).…”
Section: Venskutonismentioning
confidence: 99%
“…The suppression of GSH, GR, GPx, and GST enzyme activity was also detected in both the kidney and heart tissue. In addition, CSME showed protective effect against CCl 4 -induced DNA damage of kidney and heart tissue [117].…”
Section: Detoxification Processes Via Plant Natural Substancesmentioning
confidence: 89%
“…The % inhibition values of HCT116 (colorectal cancer) by Crataegus L. polysaccharide extract were reported as in a range from 20% to 80% between 125 and 1000 µg/mL concentrations (39). Ganie et al revealed that C. songarica methanol, ethanol and ethyl acetate extracts inhibited ~ 80%, 85%, 75% of SW480 (colorectal cancer) at 80 µg/mL concentration (40).…”
Section: Discussionmentioning
confidence: 99%